(untitled) (Bangladesh Journal of Nuclear Medicine, 2026)
Thyroglobulin (Tg) is frequently measured in follow-up of patients with differentiated thyroid carcinoma after total thyroidectomy and radioiodine therapy. A low stimulated Tg level (<1 ng/ml) associated with normal neck ultrasonography is considered as the most reliable criteria for complete remission in low-risk patients. We are reporting a case of middle-aged man with thyroid cancer and diffuse skeletal metastasis associated with low serum Tg level bringing a point of caution in evaluation of patients with low Thyroglobulin. Bangladesh J. Nuclear Med. 28(2): 379-384, 2025